(untitled) (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2021)
Schools are educational institutions that are integrated between one component and another. One of the important supporting components in educational institutions, in this case schools, is administrative staff. The role of school administration staff is very important in supporting the success and smooth running of school administration. In dealing with school administration, it requires sufficient expertise and ability in the field of administration. Therefore, human resources, in this case administrative staff, are an important component in a school. This scientific work is prepared through a literature study research methodology and observation or observation and analysis of material by the author